Explaining the Help-Seeking Intentions of Adolescents Subject to Sexual Exploitation in Tanzania: An Application of the Theory of Planned Behavior - Mlyakado, Budeba Petro (Journal of interpersonal violence, 2022)
The sexual exploitation (SE) of children and adolescents is a universal concern. Numerous empirical studies have examined the prevalence and consequences of this phenomenon worldwide, but there is little information on the factors that determine the help-seeking intentions of adolescents subject to SE in Tanzania. We drew on the theory of planned behavior (TPB) to address this knowledge gap. The study had two main objectives. First, we examined four TPB variables (attitudes toward seeking help, perceived social support, perceived social stigma, and generalized self-efficacy) as determinants of the Tanzanian adolescents? help-seeking intentions. Second, we explored the moderating effects of social stigma on the relationship between the examined TPB factors and the adolescents? help-seeking intentions. A cross-sectional survey design was used to collect data from a stratified random sample of 1,116 secondary school adolescents aged 13-17 (M = 15.66; SD = 1.09). The participants were recruited from two regions in the east and northwest of Tanzania and data were analyzed using hierarchical multiple regression. The results indicate that the TPB variables of attitude toward seeking help, perceived social support, and generalized self-efficacy were positively associated with the help-seeking intentions of adolescents subject to SE, but not social stigma. Through moderation analyses, we found that social stigma significantly weakened the explanatory power of the attitude toward seeking help. The findings of this study in the context of Tanzania were discussed and implications for policy, practice, and future research were suggested.